(untitled) (Journal of the College of Education for Women, 2019)
The researches to discover useful ways to represent the agents and agent-basedsystems are continuous. Unified Modeling Language (UML) is a visual modeling languageused for software and non software modeling systems. The aim of this paper is: using UMLclass diagram to design treasury pharmaceuticals agent and explain its internal action. Thediagram explains the movement of the agent among other nodes to achieve user’s requests(external) after it takes them. The paper shows that it is easy to model the practical systems byusing agent UML when they are used in a complex environment.